El Mediterráneo Oriental ante la llegada de los Pueblos del Mar - Pérez Largacha, Antonio (Gerión. Revista de Historia Antigua, 2003)
At the end of the Bronze Age. the Eastern Mediterranean experimented huge convulsions that affected to Empires, Status, Kingdoms and city-states from the Central Mediterranean to the Upper Mesopotamia, at the same time that new peoples and states like Philistines, Arameans, kingdoms like Moab, Edom or the settlement of Israel took place. An upheaval caused by the called «Peoples of the Sea» that, in the last years, seems more to be the consequence than the cause of this changes. Those are the reasons why being aware of the dynamics that existed in this region, characterized during the Late Bronze by the existence of fluid relationships that made possible a cultural, politic and ideological «koine » o the Mediterranean, should be a previous step to understand in their context the changes that take place and the advent of the Sea Peoples.